Intravenous leiomyomatosis: Case series and review of the literature. (August 2021) - Mathey, M.P.; Duc, C.; Huber, D.
Abstract: Introduction: Intravenous leiomyomatosis (ILV) is a rare pathology, part of leiomyoma beyond the uterus (LBU), characterized by benign smooth muscle cell tumor outside of the uterus and mainly affecting premenopausal woman with a medical history of leiomyoma or gynecologic surgical treatment. The treatment depends on the localization of the tumor, age of the patient, initial size, symptoms and the suitability for surgery but should always aims in toto surgical resection. Case presentation: Retrospective case series and review of literature. Clinical discussion: Symptoms presented by the patient were aspecific and only localized in the pelvic area. All cases were fortuitous histopathological diagnosis. No relapse was. Two out of 5 patients have pulmonary nodules, only one was biopsied and diagnosed with PBML (pulmonary benign metastasizing leiomyoma). Conclusion: IVL and BML are rare disease that can co-exist. Because of tumoral hormonal receptors, hormonotherapy could be an optional treatment but to date no clear efficacy is demonstrated. In case of high recurrence risk such as voluminous initial mass, impairment of broad ligament, failure of total surgical resection, adjuvant hormonotherapy could be useful. Recurrence rate is about 16.6-30% and can occur even dozen years later and even after radical surgery, justifying a regular follow up. Highlights: Leiomyomas beyond the uterus (LBU) is defined by benign smooth muscle cell tumor outside of the uterus. Sub classification of this entity are intravenous leiomyomatosis (IVL), benign metastasizing leiomyomas (BML), diffuse peritoneal leiomyomatosis (DPL), retroperitoneal leiomyomas and parasitic leiomyomas. The differential diagnosis of IVL should include benign myoma, thrombus, leiomyosarcoma, soft tissue sarcoma, lymphoma, cardiac myxoma, tumor thrombosis of Wilms tumor or metastasis. Treatment of IVL is usually surgery but there is no consensus about the the optimal approach. Adjuvant therapy sur as bilateral salpingoophorectomy followed by hormonothetherapy have to be balanced with their side effects. Despite being histologically benign, BML shows the metastatic potential of LBU. Because of a high rate of recurrence estimated of 16.6% to 30%, long term follow up is recommended even after radical surgery.